Cytokine soluble receptors in perinatal and early neonatal life - Efthimia Protonotariou; Demetrios Rizos; Ariadne Malamitsi-puchner; Evangelia Moira; Angeliki Sarandakou; Emmanuil Salamalekis (Mediators of Inflammation)
Background: In contrast to cellular receptors, soluble receptors do not enhance the cellular activation because they do not have transmembranic and cytoplasmic parts, acting thereby as endogenous regulatory mechanisms against systemic functions of cytokines.